2006
DOI: 10.1128/mcb.26.6.2317-2326.2006
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of dickkopf3 Mutant Mice

Abstract: dickkopf (dkk) genes encode a small family of secreted Wnt antagonists, except for dkk3, which is divergent and whose function is poorly understood. Here, we describe the generation and characterization of dkk3 mutant mice. dkk3-deficient mice are viable and fertile. Phenotypic analysis shows no major alterations in organ morphology, physiology, and most clinical chemistry parameters. Since Dkk3 was proposed to function as thyroid hormone binding protein, we have analyzed deiodinase activities, as well as thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 57 publications
3
44
0
Order By: Relevance
“…Prostate epithelial cell proliferation is increased in Dkk-3-null mice Dkk3-null mice are viable and fertile and do not show any major morphological or phenotypic alterations (del Barco Barrantes et al, 2006). To determine whether Dkk-3 affects prostate development, prostate samples were obtained from mice aged 6 and 8 weeks, when prostate development is almost complete (Sugimura et al, 1986).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prostate epithelial cell proliferation is increased in Dkk-3-null mice Dkk3-null mice are viable and fertile and do not show any major morphological or phenotypic alterations (del Barco Barrantes et al, 2006). To determine whether Dkk-3 affects prostate development, prostate samples were obtained from mice aged 6 and 8 weeks, when prostate development is almost complete (Sugimura et al, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…The details of mice deficient for Dkk-3 were described previously (del Barco Barrantes et al, 2006). Analyses were performed using male mice aged 6 and 8 weeks.…”
Section: Mouse Prostate Histology and Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that an N-terminally truncated Dkk3 encodes a substrate binding subunit, 'p29', of the type II iodothyronine 5 0 -deiodinase (D2) in rat (Leonard et al, 2000). This suggestion has not been supported (a) because of the seleno-nature of all other cloned deiodinases that act without substrate binding subunits, (b) because there is poor correlation between Dkk3/p29 and the D2 expression patterns in rat brain (MonteroPedrazuela et al, 2003) and (c) since Dkk3 knockout mice have normal deiodinase and thyroid hormone status (del Barco Barrantes et al, 2006). While Dkk3 mouse mutants are viable, they show changes in the frequency of NK cells, immunoglobulin M, hemoglobin and hematocrit levels, as well as lung ventilation.…”
mentioning
confidence: 99%
“…14,26 In order to determine if loss of Dkk-3 affects prostate tissue organization in vivo, we examined Dkk3 null mice, which are viable and do not show major morphological or phenotypic alterations. 27 Dkk3 null mouse prostates at six and eight weeks were mildly disorganized in some regions, CoMMentAry CoMMentAry a NEDD4 E3 ubiquitin ligase binding protein that is highly expressed in prostate cancer, 34 and that plays a role in TGF-β stimulation of breast cancer cell invasion and proliferation. 35 We therefore hypothesize that loss of Dkk-3 leads to activation of a subset of TGF-β target genes involved in stimulating cell invasion and proliferation, such as PMEPA1, rather than those involved in growth inhibition (Fig.…”
Section: Dickkopf-3 and The Architecture Of The Prostate Epitheliummentioning
confidence: 99%